1995
DOI: 10.1159/000276752
|View full text |Cite
|
Sign up to set email alerts
|

Ototoxicity of the New Platinum AnticancerAgent TRK-710 in Comparison with Cisplatin

Abstract: The pharmacokinetics and ototoxicity of the new platinum analogue TRK-710 (3, 9, 15 mg/kg × 3 days) were compared with those of cisplatin (1, 3, 5 mg/kg × 3). The perilymphatic concentration of TRK-710 was one seventh of that of cisplatin even 1 h after the administration. The N1 threshold of the compound action potential was elevated dose-dependently in both groups with a similar degree of hearing impairment. Morphological observation using phase contrast microscopy and scanning electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…16,128 A Phase I trial showed that TRK-710 displayed lower nephrotoxicity and myelosuppression compared with cisplatin. 129 No other Phase I or II results have been reported.…”
Section: Miboplatinmentioning
confidence: 99%
“…16,128 A Phase I trial showed that TRK-710 displayed lower nephrotoxicity and myelosuppression compared with cisplatin. 129 No other Phase I or II results have been reported.…”
Section: Miboplatinmentioning
confidence: 99%
“…Typically, it is initiated in the outer hair cells (OHCs), followed by the inner hair cells (IHCs). Hair cell damage begins at the basal turn of the cochlea and spreads gradually to the apex in vivo with an increasing drug dose [7]. In addition to damaging the hair cells, cisplatin also damages spiral ganglion neurons in the modiolus and the marginal epithelium on the stria vascularis [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Moreover, a phase I trial in Japan showed that the new platinum analogue, TRK-710, has a lesser degree of nephrotoxicity and myelosuppression. 30) Both cisplatin and carboplatin cause hematopoietic disorders as side effects, [26][27][28][29] and they are administered intravenously.…”
mentioning
confidence: 99%